Pengaruh Teknologi Swalayan dan Layanan Personal Terhadap Loyalitas Pelanggan - Sihombing, Lia (CV. Rayyan Dwi Bharata, 2025)
Many companies use self-service technology nowadays as a result of advances in technol- ogy. In the specific, those companies replace personal services with self-service technology facilities. For instance, a bank can use automatic teller machine (ATM) instead of a bank teller inside the bank. The use of self-service technologies is aimed to fulfill the variety of consumers’ needs. However, not many research focus on the impact of self-service technology on consumer satisfaction and loyalty. Therefore, the aim of this research is to test a model of the impact of self-service technology on consumer satisfaction and loyalty. This research replicated the model which was developed by Beatson et al. (2006) and extend the model by adding a variable called consumer loyalty. Questionnaires were distributed to respondents by the drop-off/ pick-up method and a total of 372 completed questionnaires were used in the analysis. The data was then analyzed using structural equation modeling. All research hypotheses were supported this paper also provides the implications for theoretical and managerial and offers directions for future research.